K teorii poleta lyzhnika pri pryzhkakh s tramplina - Bagin, N. A.; Voloshyn, Yu.; Yevteyev, V. P. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to offer the method of calculation the length of ski-jump. The offered theory allows to conclude that the length of ski-jump increases with the initial speed's aerodynamic quality of flight, angles of flying out track's slope and landing as well as with the decreasing of the head resistance.